2019
DOI: 10.1093/ofid/ofz360.1699
|View full text |Cite
|
Sign up to set email alerts
|

2019. Multicentric Antimicrobial Point Prevalence Survey in Four Tertiary Care Hospitals in Southern India

Abstract: BackgroundAntibiotic consumption data are scarce in the subcontinent. Defined Daily Doses (Doses) and Days of Therapy (DOT)-based metrics both have inherent disadvantages limiting their application in resource-limited settings primarily in terms of resource hours.. Point Prevalence Study (PPS) offers an offer an initial feasible step for describing antimicrobial use and identifying targets to reduce inappropriate use. Aim of the present study was to use PPS to identify quantitative and qualitative aspects of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…An additional 15 citations were identified from the grey literature search for a total of 123 publications (figure 1). 13–135 Of the 123 studies, 64 were peer reviewed, 53 were conference proceedings and 6 were online documents (eg, reports).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 15 citations were identified from the grey literature search for a total of 123 publications (figure 1). 13–135 Of the 123 studies, 64 were peer reviewed, 53 were conference proceedings and 6 were online documents (eg, reports).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 52 studies reported the prevalence of indication documentation 13–15 17 19 21 23 26–29 40 45–47 49 53 60 61 65 67 71 72 74 75 78 82 83 87 89 91 92 97 100–102 106 108 109 109 110 112 114 115 117 124–129 135. The median reported prevalence of indication documentation was 75%; however, there was a wide range across studies from 4% to 100% of antimicrobial orders with an indication documented, with an IQR of 51%–85%.…”
Section: Resultsmentioning
confidence: 99%